Periwayat Qadariyyah dalam Sahih Al-Bukhari - Lasna Ulhaq, Lani; Mutaqien, Husen Zaenal (Al Mudzakarah, 2024)
The relationship between hadith experts (muhadditsun) and kalam/theologians (mutakallimun) is considered disharmonious by Islamic scholars. In their interactions with the kalam experts, the hadith scholars kept a little distance from them. This concerns ideology and the right to narrate hadith. In the problem of ideology of the right to convey hadith there is a big question that can ideology be separated from the hadith it conveys? This means that in narrating a hadith, a rawi is not conveying his ideology, but only conveying the information (hadith) he gets to others even though it must contradict their ideology. The problem of finding cross-ideological narrators in the Book of Sahih al-Bukhari, this is related to the policy of Imam al-Bukhari who is known to be very strict in selecting narrators for the hadiths he narrated in his book. This research uses qualitative methods by means of literature studies, more specifically is descriptive analysis with a critical approach. Then it focused on the application of the science of al-Jarh wa at-Ta'dil and at-Takhrij al-Hadith through three stages. The orientation stage aims to collect general data related to al-Jarh wa at-Ta'dil, then the exploration stage aims to  collect more specific data related to the narrators, and finally  the analysis stage which  aims to  examine the data that has been collected. After going through the research stage, it was found that there were cross-ideological narrators, namely the Qadariyyah school in the book of Sahih al-Bukhari as many as 17 rawis, from all of them there were 56 hadiths. Then his entire narration is acceptable because it contains no invitation to his ideology. And the reason Imam al-Bukhari used these narrators was because of his devotion.